HUBUNGAN KADAR BETA.SITE APP.CLEAVING ENZYME 1, BETA-AMYLOID DAN 4 HYDROXINONENAL PLASMA DENGAN GANGGUAN FUNGSI KOGNITIF PADA PENDERITA PASCASTROKE ISKEMIK - Yuliarni Syafrita; Yanwirasti Yanwirasti; M Hasan Machfoed; Darwin Amir (Faculty of Medicine, Universitas Andalas, 2014)
Background: The levet of beta-amyloid (Ap) in the cerebrospinal fluid (CSS) can beused asa marker to detect cognitive impairment, but fhe CSS retrieval technique is invasive. so if r'snecessa4z fo find biomarkers that are relatively easy, cheap and reliable. Therefore, biomarkersthat can be measured in blood is needed.Aims: To determine fhe association of the blood levels of BACE-I, AB and 4HNE with ischemiccognitive functisn after stroke event.Methads: This study was an observational study with cross sectional design using cases andcontrols. A number af 84 patients with ischemic stroke and 42 normal subjecfs as controls wereenrolled. Cognitive function u/as assessed 3 months aftdr stroke event using MoCA-lna testand measurement of blood levels of BACE1-1, 4p40, AP42 and 4HNE was conducted within72 hours of onset of stroke. Regression statistical analysis was used to determine the mostdaminant factars related to the occurrence of impaired cognitive function after stroke event.Resuffs; ln bivariate analysis, we found a significant assocrafion between cognitive impairmentafter stroke with high blood levels of BACE1 (p = 0.004, OR = 1.714), low levels of AB40 (p =A.0001, AR = 14.80) and low /eve/s of AB42 @ = A.U7, OR = 3.44). There was no significantassociation between the blood levels of 4HNE with impaired cognitive function after strokeevent. ln multivariate analysis, we found low low plasma level of 4840, high level of BACE-1,and low level of AB42 were variables strongly related with cognitive impairment after ischemicstroke subsequently based on the strength of correlation.Canclusians: Low levels of 4840, ttigh levels of BACE-I and low ievels of Ap42 are associatedwith the incidence of impaired cagnitive functian after ischemic stroke.M(A, Volume 37, Nomor.Supl. 2, November 2014MKA, Volume 37, Nomor.Supl. 2, November 2014 http:/imka.fk. u nand.ac. id/ABSTRAKLatar Belakang : Kecacatan pascastroke diperberat oleh terganggunya fungsi kognitif. Metodediagnostik yang tersedia sekarang, tidak cukup sensitif bila digunakan sebagai upaya untukmenemukan gangguan kognitif pascastroke secara dini. Kadar beta-amyloid (AP) di cairanserebrospinal (CSS) dapat dijadikan sebagai penanda telah terjadinya gangguan kognitif,namun teknik pengambilan CSS adalah invasive, sehingga perlu dicari biomarker yang relatifmudah, murah dan dapat dipercaya. Untuk itu perlu dicarai biomarker pada plasma.Tujuan : Untuk mengetahui hubungan kadar BACE-1, AB dan 4HNE plasma dengan fungsikognitif pascastroke iskemik.Metode : Penelitian ini bersifat observasional dengan disain cross sectional, menggunakankasus dan kontrol. Mengikutkan 84 penderita pascastroke iskemik dan 42 subjek normalsebagai kontrol. Fungsi kognitif diperiksa 3 bulan pascastroke dengan test MoCA-lna danpemeriksaan kadar BACEI-1, AF40, AP42 dan 4HNE plasma dalam 72 jam onset stroke.. Analisa regresi statitistik digunakan untuk menetapkan faktor mana yang paling dominanhubungannya dengan terjadinya gangguan fungsi kognitif pascastroke iskemik.Hasil : Pada analisis bivariat, ditemukan hubungan yang bermakna antara gangguan kognitifpascastroke dengan tingginya kadar BACE1 (p=0,004, OR= 4,714), rendahnya kadar AP40(p=0,0001, OR=14,80) dan rendahnya kadar AP42 (p=0,0t7, OR=3,44). Tidak ditemukanhubungan yang bermakna antara kadar 4HNE dengan gangguan fungsi kognitif pascastroke.Pada analisis multivariat, didapatkan rendahnya kadar AB40 dan tingginya kadar BACE-1 plasma sebagai variabel yang kuat hubungannya dengan kejadian gangguan kognitifpascastroke iskemik.Kesimpulan : Rendahnya kadar AB40 dan tingginya kadar BACE-1 plasma berhubungandengan kejadian gangguan fungsi kognitif pascastroke iskemik.62